RESPONSE OF RICE VARIETIES GROWN ON CALCAREOUS AND ACID MIXED SOILS AMENDED BY VERMICOMPOST UNDER VARIABLE CLIMATES - Saha, M.K.; Khan, H.R.; Hossain, M.S.; Akter, S. (International Journal of Research -GRANTHAALAYAH, 2021)
A field experiment was conducted to explore how rice (BINA Dhan 11 and BRRI Dhan 34) responds in modified soil and climatic conditions. They were planted on artificially prepared soil beds by mixing calcareous and acid soils in 1:1 and 1:3 ratios. Soil temperature (St) was elevated up to 20C over the diurnal ones. Moisture (M) was maintained at 50%, 70%, and saturated (100%) soil conditions. Vermicompost (V) was applied at the rates of 0, 10, and 15 tha-1. The number of tillers and plant height were recorded at 25 days intervals. The maximum number of 26 and 27 tillers for BINA Dhan 11 and BRRI Dhan 34 were recorded. The longest plant height was observed with the T10 (V15M100) treatment. The treatment T3 (V15M100) resulted in maximum fresh weight of shoot and shoot dry matter production for both rice varieties in 1:3 mixed soil. Both varieties performed well in 1:3 mixed soils and elevated temperature conditions, as observed for normal soils. This evidence concluded that the improvement of calcareous and acid soils through their mixing is a successful approach and confirmed by the treatments’ usual responses on different rice growth parameters under these mixed soils.